การพัฒนาระบบประกันคุณภาพโดยบูรณาการระบบ ISO 9001:2008 และ มาตรฐานความปลอดภัย IAEA - ฐิติ นุ่มนวล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this study are to develop a quality manual and to generate of operation procedures from integrating ISO 9001:2008 and IAEA GS-R-3 system for solving issues of an Nuclear regulatory office whose mission is to regulate nuclear safety. The study examined the requirements of ISO 9001:2008 and IAEA GS-R-3 system by referring to research works related to system integration. The processes in regulating nuclear safety of the case study were also studied and 20 problematic issues was discovered. Then the current processes were compared with requirements of ISO 9001:2008 and IAEA GS-R-3. ISO 9001:2008 and IAEA GS-R-3 system are integrated. Operation procedures were designed by integrating ISO 9001:2008 and IAEA GS-R-3 system resulting in a Quality Manual which consisted of 24 operations procedures. Two procedures were implemented, namely procedures for nuclear facilities inspection group and for nuclear safety administration group. In monitoring the executed procedures, it was found that internal coordination was improved and working procedure is more complete.